Annual report of the Women's Health Care Committee, Japan Society of Obstetrics and Gynecology, 2020. Issue 1 (21st October 2020) - Kato, Kiyoko; Terauchi, Masakazu
Abstract: Our committee was founded in 2010 with the goal of improving women's health. This academic year, we focused on five activities: cooperation between the departments of pediatric surgery and obstetrics and gynecology for the treatment of persistent cloaca and Mayer–Rokitansky–Küster–Hauser syndrome in Japan; assessment of the educational training of women's health‐care advisers; increasing screening for breast and cervical cancer; conducting the Nationwide Survey of Prescribing Practices for the Treatment of Menopausal Symptoms; and preventing osteoporosis in survivors of gynecologic cancer. The activities of each subcommittee are detailed below. This report is based on the Japanese version of the annual report ( Acta Obst Gynaec Jpn 2020;72(6):697–707).